Genetic Characterization of Piroplasms in Donkeys and Horses from Nigeria - Sunday Idoko, Idoko (Animals (Basel), 2020)
SIMPLE SUMMARY: Theileria equi and Babesia caballi are blood-parasites of horses and donkeys that are transmitted by ticks and may cause severe clinical illness. Many infected animals are carriers of parasites without showing signs of disease and, thus, pose a risk of transmission. Nigeria is a major passageway in animal import, export and transport within Africa. This movement of animals may play a key role in the spread of parasites. The aim of this study was to characterize these parasites that infect both horses and donkeys in Nigeria. Blood was collected from horses and draught-donkeys at two separately-owned farms in northern Nigeria. Infection with T. equi was detected in both donkeys and horses, with four of the five known genotypes present in Africa. Infection with a single genotype of B. caballi was detected in donkeys. Our results suggest that donkeys may be an important reservoir of these parasites. The high diversity of T. equi supports the hypothesis that animal transport through Nigeria may contribute to the spread of parasites to and from other countries in the region. ABSTRACT: Equine piroplasmosis (EP) is a tick-borne disease of equids, caused by the two haemoprotozoal parasites: Theileria equi and Babesia caballi. Nigeria constitutes a major crossroads of animal transport in West Africa and may serve as a factor in EP dissemination in the region. The study aim was to characterize EP parasites in donkeys and horses in northern Nigeria using a molecular approach. Blood was collected from 57 donkeys and 47 horses. EP infection was detected and characterized by polymerase chain reaction (PCR). Twenty five donkeys (43.8%) were infected with T. equi, five (8.8%) with B. caballi, three (5.3%) with dual infections. Four horses (8.5%) were infected by T. equi and none by B. caballi. Four of the five known T. equi 18S rRNA genotypes (A, B, C and D) were identified. Theileria equi ema-1 and ema-2 genes were amplified in only 2 and 10 samples, respectively, showing no genetic variation. All B. caballi isolates were classified as rap-1 genotype A1. Twenty-two (42.3%) of the donkeys were positive for anti-T. equi antibodies and 29 (55.8%) were positive for anti-B. caballi antibodies, using immunofluorescence antibody test (IFAT). The study results demonstrate high genetic variation within T. equi parasites, suggesting that donkeys may be reservoirs of EP parasites in West Africa.